Pelatihan Branding dan Digital Marketing untuk Meningkatkan Nilai Jual pada UKM Vigaza Farm - Andriani, Ria; Astria, Kadek Kiki; Sunyoto, Andi (Politeknik Negeri Cilacap, 2025)
As part of the Sleman Millennial Farmers Group, Vigaza Farm SME has great potential in developing quail farming products. However, this business is still hampered by issues related to brand identity management, packaging design quality, and suboptimal digital marketing strategies, which have implications for low sales value and competitiveness. Through community service activities, this program focuses on enhancing branding and digital marketing capabilities for the managers of Vigaza Farm. The training was conducted on June 21, 2025, at Building 2 of Amikom University Yogyakarta, attended by 10 participants comprising owners, staff, and internal members. The implementation methods included socialization, training, technology application, as well as mentoring and evaluation. The materials covered basic branding concepts, visual identity creation (logo, brand colors, typography), packaging design development, and an introduction to simple digital marketing strategies. Evaluation results showed a significant improvement in participants' understanding. Before the training, 75% of participants were in the “understand” category (score 4) and 25% in the “very understand” category (score 5). After the training, 75% of participants were in the very knowledgeable category (score 5) and 25% in the knowledgeable category (score 4). This activity produced two ready-to-use packaging designs, namely “Sambal Telur Puyuh Kencana” and “Puyuh Kencana Frozen,” which met branding principles and were suitable for promotion. These results demonstrate the effectiveness of the training in enhancing branding and digital marketing skills, although further guidance is still needed for optimizing online promotions.